A novel strain-based assessment method of compressive buckling of X80 corroded pipelines subjected to bending moment load. (October 2021) - Shuai, Yi; Wang, Xin-Hua; Feng, Can; Zhu, Yue; Wang, Chun-Lan; Sun, Tao; Han, Junyan; Cheng, Y. Frank
Abstract: This work presents an investigation on the compressive strain capacity of resisting buckling on an X80 steel corroded pipeline subjected to a bending moment using nonlinear finite element analysis (FEA) validated by full-scale tests. The modelling results indicate that the existing strain-based assessment method is not suitable for pipelines with deep corrosion and has certain application limitations. Consequently, a new evaluation method based on far-field strain was developed to predict the buckling failure of corroded pipelines subjected to bending loads. The influence of the corrosion shape type, corrosion size (i.e., depth d, length L, and width w ), pipe geometry, and internal pressure on the critical buckling strain capacity and critical buckling moment of the pipeline were studied using parameter sensitivity analysis to verify the proposed strain criteria. The results illustrate that the variation trends between the critical buckling strain and the critical buckling moment with each factor were consistent, indicating that the proposed novel strain-based evaluation method is effective and applicable. In addition, the buckling resistance of a pipeline with rectangular corrosion is relatively weaker than that with a semi-spherical corrosion pit or cylindrical grooved corrosion under the same defect size. Further, the critical compressive strain capacity of a corroded pipeline is primarily affected by the depth and width of the corrosion, whereas the effect of the corrosion length is relatively insignificant. Moreover, the critical length and width of the corrosion defect affecting the bending capacity of resisting buckling were determined as L / D t = 20 and w / π D = 0 . 5, respectively. Highlights: A novel strain-based assessment method of local buckling of corroded pipelines. Determined the effect of defect geometry on critical compressive strain capacity. Determined the critical defect size that affect the pipe buckling strain capacity.